SAT0451 The one-year radiographic progression and minimal disease activity in early psoriatic arthritis patients treated according to treat-to-target strategy (results of an ongoing open-label remarca study). (15th June 2017) - Loginova, E; Korotaeva, T; Smirnov, A; Koltakova, A; Karateev, D
Abstract : Background: Treat-to-target (T2T) strategy has benefit in early psoriatic arthritis (EPsA) treatment. Its influence on radiographic progression has limited data. Objectives: to investigate radiographic outcomes and minimal disease activity (MDA) after 1-year of T2T strategy in patients with EPsA. Methods: 40 (M-18/F-22) DMARD-naïve pts with active EPsA, according to the CASPAR criteria, mean age 38.4±11.1 yrs., PsA duration 11.9±10.6 months, psoriasis duration 73.8±84.6 months, median DAS 3.8 [3.2; 4.7] from the open-label REMARCA study were included. At baseline all pts were treated by Methotrexate (MTX) subcutaneous (s/c) 20–25 mg/week. Pts that still had medium or high activity after 3–6 months were treated by combination therapy MTX+ biologic therapy (BT) - anti-TNF or Ustekinumab (n=21). By the end of the study, 19 pts were treated by MTX-monotherapy. At baseline and after 1-yr. of treatment PsA activity index and digital radiographs of hands and feet were performed. All images were scored according to Sharp/van der Heijde (Sh.-v.d. H) method by a blinded musculoskeletal radiologist. Median total score (TS Sh.-v.d. H) = total erosion score (TES) + total narrowing score (TNS), the proportion of pts who reached MDA, M±SD, Me [Q75; Q50], W-test, U-test, (%) were calculated. All p<0.05 were considered to indicate statistical significance. Results: At baseline, 23 out of 40 pts (57%) had erosion. By 1 yr., the number of pts with erosion increased up to 26 pts (65%). The median TS Sh.-v.d. H significantly increased from 91.5 [72–108.5] to 91.5 [73.5–111.5] (W-test, p<0.01), TES from 2 [0–4.5] to 2.5 [0–5] (W-test, p<0.05) and TNS from 85 [69–105] to 87 [71.5–107] (W-test, p<0.01). At 1 yr. of therapy there was no significant difference between the treatment groups in the value of TS Sh.-v.d. H (W-test p>0.05). 25 of pts (62.5%) had reached MDA by 1 yr. In pts who did not reach MDA (n=15) by 1 yr. TES was significantly higher at baseline compare to those who reached MDA: 3 [2–9] and 0 [0–3] accordingly (U-test, p<0.05). In the group of pts who did not reach MDA 1 yr. progression was significantly higher (table). In 29 out of 40 pts (72.5%) there was no X-ray progression considering both erosion and joint space narrowing. 13 of them (45%) were treated by MTX and 16 pts (55%) by MTX+BT. Negative X-ray progression was found in 11 out of 40 pts (27.5%): 6 of them (54.5%) were treated by MTX and 5 pts (45.5%) by MTX+BT. Conclusions: In the Russian cohort of active EPsA pts erosion was found in more than half of cases. Active EPsA pts treated according to T2T strategy during 1 year in 72.5% did not show any radiographic progression, only a quarter of pts (27.5%) had negative X-ray progression by the end of the study, regardless of the type of therapy. The pts who achieved MDA had less erosive progression. Disclosure of Interest: None declared